Techne in the Digital Age: A Lakatosian Reading of Bernard Cache's Tool-Making Practice - Torlak, Ilayda; Kaymaz, Senem (MDPI, 2026)
This study reexamines the concept of techne within computer-aided architectural practices and proposes a Lakatosian research program framework to understand its historical continuity and contemporary transformation. Since its ancient origins, techne has been not only a knowledge of making but a mode of thinking and knowing that unifies mental and material production within a single practice. To analyze its transformation, Imre Lakatos's methodology of research programs is adopted as a framework, and techne is examined as a research program. Within this framework, the hard core of techne is defined as the craftsman-tool-material-knowledge relationship grounded in the unity of making and knowing, while code, software, parametric systems, and algorithmic feedback mechanisms are interpreted as components of the protective belt in the digital age. The study specifically focuses on the relationship between the designer and the tool. Bernard Cache's Objectile practice is presented as a case study that illustrates the architect's transformation in the digital age from a user of tools to a developer of tools. The findings reveal the following principal patterns: tool development emerges as a conceptual necessity and an epistemic act; knowledge in digital practice acquires a hybrid structure between explicit and tacit knowledge; and feedback loops reshape not only design but also the tool itself. Consequently, techne is repositioned as a progressive research program that remains productive in architecture at both theoretical and operational levels.
Keywords: techne; digital craft; research programmes; tool making; Imre Lakatos; Construction & Building Technology; Engineering